Dynamics of social class, race, and place in rural education - Howley, Craig B. (Emerald Publishing Limited : Information Age Publishing, Inc., 2014)
Half the world's population lives in rural places, but education scholars and policy makers worldwide give little attention to rural of education. Indeed, most national systems, including in the developed world, treat their educational systems as institutions to 'modernize' the global economy.The authors in this volume have different concerns. They are rural education scholars from Australia, Canada, the United States, and Kyrgyzstan, and here their focus is the dynamics of social class: in particular rural schools but also in rural schooling as a local manifestation of a national (and the global) system.For the most part, the volume comprises relevant empirical reports, but none neglects theory, and some privilege theory and interpretation. First and last chapters introduce the texts and synthesize their joint and separate meanings. What are the implications of place for social class? How do class dynamics manifest differently in more and less racially homogeneous rural communities? How does place affect class and how might class affect place? How does schooling in rural communities reproduce or interrupt social-class mobility across generations? The chapters engage such questions more completely than other volumes in rural education, not as a final word or interm summary, but as an opening to an important line of inquiry thus far largely neglected in rural education scholarship.